(untitled) (قضايا سياسية, 2023)
Abstract Studying the role of international powers in the transformations of the international system and predicting the future roles of these countries is considered as the focus of interest particularly for those interested in international and geopolitical studies. One of these powers has been studied, as well as its place in the structure of the international system ,its building factors, and its future have been predicted. This power is represented by (China). The research problem is presented in answering the following main question: What is the impact of Chinese geopolitics on the transformations of the international system? In addition to several questions, and to answer the questions, the method of multiple approaches is adopted, as the descriptive analytical approach has been adopted in addition to the forward-looking approach, and the research has reached the following results, the most important one is that power is the main engine of the international system which is characterized by mobility and dynamism, and the concept of influential power is not limited to the military aspect only, but also has its influence on the cultural and economic aspects. As a result of that, the economic power of China has had an effective influence in enabling China to have an active role in the international system, and that the strategy of China that has the features of which are drawn through its economic initiative “One Road - One Belt”, which do not stop at the economic aspect only, but also include political aspects, by which China will seek to strengthen its ties with all countries, and establish modern contracts and alliances, particularly , establishing an international alliance with Africa against the control of Western powers and their imposed laws.